A Case of Multiple Mandibular Molar Extractions for a Hemophilia a Patient - Aesa Alzaroug Jaber; Alshame M. J. Alshame; Prabhu Manickam Natarajan; Asok Mathew (Indian Journal of Forensic Medicine & Toxicology, 2021)
Hemophilia A is a genetic coagulation disorder associated with a deficiency of clotting factor VIII. It can be inherited or acquired and have different levels of severity. The present case report describes a Libyan male patient with Factor VIII deficiency who underwent multiple remaining roots extraction.The patient was a 26-year-old Libyan male with history of hemophilia A of mild type. The patient underwent blood tests and imaging to assess the severity of hemophilia and the condition of the surgical area. The blood examination revealed normal Bilirubin level (0.6), low levels of, RBC (4.55), HGB (10.9), PT (17.7) and slight changes in platelet count and Factor VIII level. The treatment plan for the day of surgery was accordingly, the patient was administered Factor VIII 24 hours before the day of surgery. The patient underwent the multiple roots extraction of lower left first and second molar under local anesthesia using 2% Lidocaine with 1:80, 000 Adrenaline. The Injection technique was regional nerve block (inferior alveolar, Lingual, and long buccal nerve block).After extraction, direct pressure on the area using a damp gauze swab, maintained for at least 30 min, a hemostat and multiple thread suture were applied. One hour after surgical removal of the roots again the patient administered Factor VIII.There was no subsequent bleeding or complications at follow-up in the first three days. In the fourth day there was moderate bleeding at the extraction sockets continued for a day. At fifth day the patient was admitted at the Sebha Medical Centre. The bleeding stopped after 24 hours. Treatment plan in the Medical Centre was administration of factor FVIII, tranexamic acid 500 mg three times a day and vitamin K once a day. All injections were given intravenously. Then the patient discharged from the Centre in the sixth day after bleeding controlled. The wound had healed completely without abnormalities.